Accident prevention system using Ultrasonic range Sensor with intelligent Braking Methodology - Safwan Sadi, Digambar Bisht, Saharsh, Sagar, Rahul Raj. (International Journal of Control and Automation, 2020)
Traffic accidents are one of the most severe issue that fatalities more than 1.3 million world’s population every year. Proposed idea to mitigate the effect of road accident by detecting obstruction. The autonomous circuit designed on Arduino UNO platform programmed in block for processing raw data and interfacing. A combination Pyroelectric infrared and ultrasonic range sensor to measure the obstacle distance along with piezo buzzer for prior auditory warning. If approaching distance is less than the specified instantly, sensor signals will be transformed into pulses of electricity to reduce the speed of vehicle gradually in different blocks by applying frictionless Electromagnetic breaking automatically and could stop at extreme, smoothly to avoid any crashes. The motion will be resumed in absence of electric pulses shortly. Schematic design has been successfully tested on Proteus 8 software and this could be implemented in existing model with minor alteration. Motive of disclosure to commercialize this cost-effective reliable mechanism with elevating safety than previous one developed to inhibit such unintended casualty.